Conectando-c: a influência da internet na vida dos portadores de Hepatite C - Guimarães, Graziele Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Hepatitis C is a disease that affects approximately four million Brazilians. It is a rare disease with symptoms but with a treatment that involves marked secondary effects. The silence of their symptoms, however, socially projected, build the social imaginary figures that send feelings and prejudices, being born therefore the social stigma. This situation fundamentally affects the welfare of their subjects. In this aspect, this research traces a parallel between the situation experienced by patients with hepatitis C and the use for these individuals from the World Wide Web and its interactive tools on overcoming limits the disease and in the reconstruction of their social identities.

A hepatite C, doença que afeta cerca de quatro milhões de brasileiros, é uma enfermidade de raros sintomas, mas com um tratamento que acarreta fortes efeitos secundários. O silêncio de seus sintomas, entretanto, projeta-se socialmente, construindo no imaginário social figuras que carregam sentimentos e preconceitos, nascendo, assim, o estigma social. Essa situação afeta fundamentalmente o bem-estar de seus portadores. Neste aspecto, a presente pesquisa traça um paralelo entre a situação vivenciada pelos portadores de hepatite C e a utilização por esses indivíduos da rede mundial de computadores e suas ferramentas de interação na busca da superação da doença e na reconstrução de suas identidades sociais
Keywords: Estigmatização; Hepatite C; Internet; Redes sociais on line; Stigma; Hepatitis C; Internet; Social networks